Avaliação do serviço de coleta de resíduos sólidos domiciliares em cidade de médio porte utilizando sistemas de informações geográficas e receptores do sistema de posicionamento por satélite - Castro, Leonardo Borges (2006)
This work presents the case study of the domestic waste collection from Monday to Saturday done by City Hall in downtown of Ituiutaba City (MG) which has almost 90.000 inhabitants. To characterize this problem, mapping of the sectors and routes were done in this area with Global Positioning System (GPS) receivers and the software GPS TrackMaker was used for data support to calculate distances, times and speeds. Afterwards, the Geographical Information System (GIS) was used as tool for vehicle routing in waste collection service. The TransCAD release 4.5 which is a transportation GIS, known GIS-T, was running for arc routing procedures. The use of GPS receivers showed itself as an important and efficay tool for data collection and mapping the routes travelled by the vehicles. The results of TransCAD running showed 44 % reduction in link overpass, 71 %reduction in labor and 68 % reduction in distances travelled comparing the current situation.